Emergence of shape and flow structure in Nature in the light of Constructal Theory. - Reis, A. Heitor (2012)
3.1 Introduction 3.2 Architectures of particle agglomeration 3.3 Flow architectures of the lungs 3.4 Scaling laws of river basins 3.5 Scaling laws of street networks 3.6 The Constructal Law and Entropy Generation Minimization 3.7 How the Constructal Law fits among other fundamental principles 3.8 Conclusion